Andres Bonifacio theorizing the nature, origins & involution-proliferation of the Philippine culture of corruption : how Rizal & the illustrado youth of the 1880s & 1890s betrayed the revolution & the Filipino people... - De Guzman, Domingo Castro ([Place of publication not identified publisher not identified], 2012)
"The works being made public in this book are my further attempts to contribute to the sanity of this nation-- more specifically, to the rooting out of this country's world-famous culture of corrution-- and to a dream of securing the foundations, for the first time--of course!--of a real intellectual culture."--Preface.
Keywords: Corruption -- Philippines; Philippines -- History -- 1812-1898.; Philippines -- History -- Revolution,1896-1898.